WALCOM: Algorithms and Computation 7th International Workshop, WALCOM 2013, Kharagpur, India, February 14-16, 2013. Proceedings - Ghosh, Subir Kumar; Tokuyama, Takeshi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 7th International Workshop on Algorithms and Computation, WALCOM 2013, held in Kharagpur, India, in February 2013. The 29 full papers presented were carefully reviewed and selected from 86 submissions. The papers are organized in topical sections on computational geometry, approximation and randomized algorithms, parallel and distributed computing, graph algorithms, complexity and bounds, and graph drawing.
Computational Geometry -- Approximation and Randomized Algorithms -- Parallel and Distributed Computing -- Graph Algorithms -- Complexity and Bounds -- Graph Drawing.
Keywords: Computer science; Computer software; Computational complexity; Algebra -- Data processing; Computer graphics; Algorithms; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Math Applications in Computer Science; Symbolic and Algebraic Manipulation; Computer Graphics; Algorithms